Financial intelligence for entrepreneurs : what you really need to know about the numbers - Berman, Karen, 1962- (Harvard Business Press, 2008)
"In this essential guide, Karen Berman and Joe Knight customize the approaches and insights from their acclaimed book Financial Intelligence specifically for entrepreneurs. The authors not only demystify common financial terms and tools, they also show how you can use this knowledge to gauge your company's performance and make better decisions."-back cover.